PSYCHOLOGICAL BARRIERS IN LEARNING ENGLISH FOR MEDICAL PURPOSES: EVIDENCE FROM INDONESIAN MIDWIFERY STUDENTS - Andri Donal; Ratna Dewanti; Ninuk Lustyantie (English Study Program University of Pasir Pengaraian, 2026)
Psychological factors are increasingly recognized as important influences on students’ success in English for Specific Purposes (ESP), particularly in healthcare education where effective communication is essential. This mixed-methods study investigated the affective and cognitive barriers experienced by midwifery students in learning English within an English for Medical Purposes (EMP) context. Questionnaire data were collected from 120 midwifery students, while twelve participants were purposively selected for semi-structured interviews to provide deeper insights into their learning experiences. The study was informed by perspectives from foreign language anxiety, self-efficacy, and cognitive load theories. The findings revealed that low self-confidence (62%), language anxiety (60%), and cognitive overload (58%) were the most frequently reported barriers. These factors were associated with reduced classroom participation, communication avoidance, difficulties in recalling specialized vocabulary, and lower confidence in performing speaking tasks. Qualitative findings further showed that fear of negative evaluation, perfectionism, and test anxiety often intensified students’ reluctance to use English in academic and simulated clinical settings. The findings suggest that challenges in EMP learning extend beyond linguistic knowledge and are closely connected to students’ emotional and cognitive experiences. Several pedagogical strategies emerged as particularly relevant, including simulation-based communication activities, scaffolded vocabulary instruction, collaborative learning tasks, and low-stakes assessment practices. By addressing both language development and psychological support, EMP instruction may better prepare midwifery students for professional communication in healthcare settings.